Synthesis and characterization of acylated low molecular weight chitosan and acylated low molecular weight phthaloyl chitosan - Rahadian Permadi,; Vicit Rizal Eh Suk,; Misni Misran, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Oral drug delivery is one of the most convenient routes due to its painless administration and high patient compliance. However, oral administration is becoming more difficult to be conducted due to its poor water solubility, poor dissolution rate, and low oral bioavailability in the gastrointestinal tract. Herein, we develop a strategy to produce a chemically modified chitosan using depolymerization and introducing hydrophobic groups onto the chitosan backbone through acylation. By modifying the structure of chitosan, we aim to overcome limitations of drug delivery before and after the oral administration. The successful acylation of protected (using phthalic anhydride) chitosan and unprotected (without phthalic anhydride) chitosan was proved by Fourier transform infrared (FTIR). FTIR was conducted not only to characterize the functional group changes but also to find quantization of degree of acylation (DA) and the degree of substitution (DS) of chitosan before and after acylation. The particle size of chitosan was found ranges from 300-500 nm with zeta potential value shifted from -50 mV to a more positive value as acid anhydrides concentration increased. The Field Emission Scanning Electron Microscopy (FESEM) images showed the low molecular weight of chitosan and acylated chitosan nanoparticle possess non-spherical form with hollow structure. In addition, the size obtained was in accordance with the size measured by particle size. Hydrophobically modified chitosan has been successfully synthesized via acylation on both primary hydroxyl and amine groups on the backbone of chitosan. This chemically modified chitosan can enhance drug solubilization as well as improving biocompatibility and degradability.